ANALISIS KERANGKA KONSEPTUAL, BENTUK, SERTA TEKNIK PEMILIHAN MODEL PEMBELAJARAN PAI - Najikh, Muhammad Ainun; Datyani, Atha Rafidatunnailah; Syahdan, Muhammad Zayyan; Fauziah, Eka Rifna (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This article aims to analyze in depth the process of selecting learning models in the context of Islamic Education. This research used a qualitative approach with the type of library research. The research sources for this article were books and relevant research journals. The results of this discussion show that; First; The learning model in Islamic Education is developing to make learning better, by taking into account what must be taught, how the teacher plays a role, and how the learning atmosphere is set. Second; Learning in Islamic Education involves various models, such as lectures, group discussions, case studies, project-based learning, problem-based, simulation models, technology-based, art-based, and experience-based, which enable students to understand Islamic religious teachings more deeply through a variety of practical learning experience. Third; In choosing an Islamic Education (PAI) learning model, it is important to consider student characteristics, learning objectives, available technology, development of critical skills, and collaborative cooperation to create a learning environment that supports a deep and relevant understanding of Islamic Religious Education. It is hoped that this article can provide knowledge and assistance to educators in designing appropriate learning models, especially in the context of Islamic Education. With a good understanding of learning models, it is hoped that the learning objectives, especially in the field of Islamic Education, which have been discussed can be achieved.